2016
DOI: 10.1158/1535-7163.mct-15-0172
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Therapeutic Resistance to ERK Inhibition

Abstract: The MAPK pathway is frequently activated in many human cancers, particularly melanomas. A single-nucleotide mutation in BRAF resulting in the substitution of glutamic acid for valine (V 600E ) causes constitutive activation of the downstream MAPK pathway. Selective BRAF and MEK inhibitor therapies have demonstrated remarkable antitumor responses in BRAF V600E-mutant melanoma patients. However, initial tumor shrinkage is transient and the vast majority of patients develop resistance. We previously reported… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 32 publications
2
42
0
Order By: Relevance
“…A study using random mutagenesis, identified some of the on-target ERK mutations that confer resistance to V11e (36). Consistent with our findings, a recent study involving S984 ERKi identified the G186D ERK1 mutation in HCT116 cells as a cause of resistance to S984 (37). Structural analysis of the ERK indicated that the mutations affect the binding of ERK-inhibitors and thus prevent them from blocking ERK activity.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…A study using random mutagenesis, identified some of the on-target ERK mutations that confer resistance to V11e (36). Consistent with our findings, a recent study involving S984 ERKi identified the G186D ERK1 mutation in HCT116 cells as a cause of resistance to S984 (37). Structural analysis of the ERK indicated that the mutations affect the binding of ERK-inhibitors and thus prevent them from blocking ERK activity.…”
Section: Discussionsupporting
confidence: 88%
“…S3A). Consistent with our findings, expression of ERK1 and ERK2 mutants were previously reported to confer ERKi resistance in A375 and HCT116 cells (36,37,61). These findings confirm that the on-target mutations are sufficient to confer resistance to ERK inhibitors against which they arose.…”
Section: Erk1/2 Mutant Erki-r Cells Are Sensitive To An Alternate Erksupporting
confidence: 92%
See 2 more Smart Citations
“…This may suggest that acquiring resistance to ERK1/2-targeting agents is harder to achieve than acquiring resistance to BRAF or MEK therapy. However, in vitro studies with other ERK1/2 inhibitors have identified specific mutants in ERK1/2 that drive resistance (39,40); these specific mutations have yet to be identified in clinical samples from ERK1/2 inhibitor-relapsed patients.…”
Section: Discussionmentioning
confidence: 99%